Una nueva especie de afido (Hemiptera: Aphididae) detectada en Chile: Sipha flava (Forbes) - Gonzalez, W.L:=700 1 Fuentes Contreras, E.; Niemeyer, H.M.
(Es, En)
Ilus., 16 ref.
Keywords: HEMIPTERA; APHIDIDAE; APHIS; TAXONOMIA; ESPECIES NUEVAS; REGISTRO; CHILE; SIPHIA FLAVA; REVISTA CHILENA DE ENTOMOLOGIA